2015
DOI: 10.1093/bja/aev104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sugammadex on incidence of postoperative residual neuromuscular blockade: a randomized, controlled study

Abstract: Clinicaltrials.gov:NCT01479764.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
151
5
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(169 citation statements)
references
References 38 publications
4
151
5
4
Order By: Relevance
“…Alternatively, the challenge of cells with SGX or other structurally similar agents can modulate K V 3.1 channels where the closed channel conformation represents the high-affinity binding site. It also needs to be noted that, according to minimal reaction scheme shown here, the dissociation constant for SGX treatment was calculated to be 17.5 μM, a value that can be clinically achievable [1, 3, 5]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the challenge of cells with SGX or other structurally similar agents can modulate K V 3.1 channels where the closed channel conformation represents the high-affinity binding site. It also needs to be noted that, according to minimal reaction scheme shown here, the dissociation constant for SGX treatment was calculated to be 17.5 μM, a value that can be clinically achievable [1, 3, 5]. …”
Section: Discussionmentioning
confidence: 99%
“…Sugammadex (SGX) is recognized as a modified γ-cyclodextrin with a lipophilic core and a hydrophilic periphery, and it has been used clinically for reversal of neuromuscular blockade caused by rocuronium or vecuronium during general anesthesia [15]. A previous report showed that addition of SGX could cause neuronal apoptosis in primary cultures [6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore it was suggested that the association between NMBAs and POPCs was dose-dependent (5,12,71,72). These studies severely criticized, were limited by many factors like the accuracy of data collection, insufficient propensity scoring and the questionable efficacy of qualitative neuromuscular monitoring (69,73).…”
Section: Debatementioning
confidence: 99%
“…In a recently pub-lished randomized study of 150 patients undergoing abdominal surgery [3] sugammadex was compared to neostigmine in terms of residual paralysis incidence in the PACU. No patient had residual paralysis after reversal with sugammadex (0 out of 74) compared to 43% after neostigmine (33 out of 76) usual care patients.…”
Section: Why Prefer Sugammadex?mentioning
confidence: 99%